A Optimizing Helmet Production Quality Using The Six Sigma DMAIC Approach and FMEA - Abdan Syaker; Joumil Aidil (ITEJ (Information Technology Engineering Journals), 2025)
This study was conducted to analyze the main causes of defects in the Bogo helmet production process at PT Sidoarjo Helmet. The research method used is Six Sigma with DMAIC (Define, Measure, Analyze, Improve, Control) approach combined with FMEA (Failure Mode and Effect Analysis) analysis. This research was conducted during the period January-December 2024 with a total inspection of 44,249 units and a total defect of 4,670 units. The purpose of this research is to identify the types of defects that occur most frequently, calculate DPMO values and sigma levels to determine the capability of the production process, and provide suggestions for improvement based on the priority of failures found. Based on the calculation results, the DPMO value is 433,860 which shows that the level of defects is still relatively high, with a sigma level of only 1.67. The results of the FMEA analysis show that bubbly paint has the highest RPN (Risk Priority Number) value, so it is the main focus of improvement efforts. Suggested corrective actions include improving operator training, strengthening work procedures, and controlling the quality of raw materials and production processes. At the control stage, the company is advised to implement regular quality control using control maps and internal audit systems. This research is expected not only to reduce the product defect rate, but also to improve the process efficiency and competitiveness of the company in the national helmet market.